Type III effector VopC mediates invasion for Vibrio species - Zhang, Lingling (2012)
Vibrio ssp. are associated with infections caused by contaminated food and water. A Type III Secretion System (T3SS2) is a shared feature of all clinical isolates of V. parahaemolyticus and some V. cholerae strains. Despite being responsible for enterotoxicity, no molecular mechanism has been determined for the T3SS2-dependent pathogenicity. Here we show that although Vibrio ssp. are typically thought of as extracellular pathogens, the T3SS2 of Vibrio mediates host cell invasion, vacuole formation and replication of intracellular bacteria. The catalytically active effector VopC is critical for Vibrio T3SS2 mediated invasion. There are other marine bacteria encoding VopC homologues associated with a T3SS and, therefore, we predict that these bacteria will also likely to use T3SS mediated invasion as part of their pathogenesis mechanisms. These findings suggest a new molecular paradigm for Vibrio pathogenicity and modify our view for the roles of T3SS2 effectors translocated during infection.